Potential role of viral metagenomics as a surveillance tool for the early detection of emerging novel pathogens - Mohsin, Hareem (Arch Microbiol, 2020)
Since the early times, human beings have always been faced with deadly microbial infections, both bacterial and viral. Pathogens such as viruses are always evolving owing to the processes of antigenic shift and drift. Such viral evolution results in the emergence of new types and serovars that prove deadly for humans-like influenza pandemics, severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). The pandemic of novel coronavirus SARS-CoV-2 is the recent example. It has resulted in a great loss of human lives and a serious burden on economy across the globe. To counter such situations, a system should exist for the early detection of emerging viral pathogens. This will help prevent possible outbreaks and save human lives. Most of such deadly novel viruses and viral outbreaks are known to be originated from animal hosts. Regular monitoring of potential hot spots of such emerging microbes, such as zoos and animal markets, through metagenomics could help assess the presence of new viruses and pathogens. In this review, we focus on the potential of viral metagenomics and propose a surveillance system based on it for the early detection and hence prevention of such emerging viral infections.